Motor neurone disease: molecular basis - Talbot, Kevin (Henry Stewart Talks, 2007)
Models of MND pathogenesis, Current understanding on genetic basis of MND, Animal and cellular models, Pathways of motor neurone vulnerability, Abnormal protein handling, Mitochondrial dysfunction, Abnormalities in axonal transport and apoptosis, Current limitations in treatment, Role of genetic research in identifying biological basis, Future directions and developing biomarkers
Archived at 2016/06/22